CFH, VEGF and HTRA1 promoter genotype may influence the response to intravitreal ranibizumab therapy for neovascular age-related macular degeneration. Issue 2 (10th May 2011) - McKibbin, Martin; Ali, Manir; Bansal, Shveta; Baxter, Paul D; West, Kumi; Williams, Grange; Cassidy, Frances; Inglehearn, Chris F
Abstract : Aims: To investigate an association between genotype for three single nucleotide polymorphisms strongly associated with the development of age-related macular degeneration (AMD) and the early response to treatment with intravitreal ranibizumab for neovascular AMD. Methods: Best corrected visual acuity letter score was recorded at baseline and each subsequent visit. Age, sex, smoking history, lesion type and the number of injections were also recorded. Genotypes were obtained for rs11200638 in HTRA1, rs1061170 in CFH and rs1413711 in VEGF . Data were analysed with treatment response at month 6 as both a binary (>5 letter improvement vs ≤5 letter gain) and a linear trait. Results: This initial study cohort consisted of 104 Caucasian neovascular AMD patients treated with intravitreal ranibizumab. Trends towards a more favourable outcome were seen with the higher AMD risk genotypes in CFH and VEGF in both the linear and binary models and in HTRA1 in the linear model alone. For CFH, mean letter score change after 6 months was +1.6, +5.9 and +7.2 letters for the TT, TC and CC genotypes and a >5 letter gain was seen in 34.6%, 56.6% and 56%, respectively. For VEGF, mean letter score change after 6 months was +1.3, +5.8 and +7.4 letters for the TT, TC and CC genotypes and a >5 letter gain was seen in 40%, 55.8% and 51.9%, respectively. For HTRA1, mean letter score change was +2.2, +7.5 and +2.9 letters for the GG, GA and AA genotypes. Conclusions: This study reports preliminary evidence suggesting that the higher AMD risk genotypes in CFH, VEGF and HTRA1 may influence the short-term response to treatment with ranibizumab for neovascular AMD.